Perancangan Dashboard Penilaian Tim Merchandising PT. Astro Technologies Indonesia - Deistata Majiore; Wasino; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
Companies in achieving a company's goals must understand the performance of each team in the company. In overcoming and supervising that each team has achieved a goal and has performed well, a dashboard is needed to provide information and also help a company achieve its goals in understanding and monitoring the performance of each team and its members. The dashboard is made using a UCD (User Centered Design) method, a method that focuses on user behavior as the basis for creating a system. With this method, the dashboard will become a monitoring, evaluation tool, and become a report for a merchandising team in meeting the needs of a company. By making this dashboard, it will be very easy for users to understand and assess the performance of existing members and teams and with the design of existing KPIs it can facilitate the assessment of members and the merchandising team.